2019
DOI: 10.1177/1177180119893132
|View full text |Cite
|
Sign up to set email alerts
|

Ancestors’ times and protection of Amazonian Indigenous biocultural heritage

Abstract: This article discusses how for the Apurinã community in Brazil, the relationships with certain places and nonhuman entities actually co-produce biocultural heritage. This involves not only storytelling, care, and respect, but also avoidance, and thus shows specific intergenerational ways of managing and relating to the land. Here I will especially address Apurinã ancestral forest and historical places, and the experiences and knowledge that they trigger, including stories of Apurinã ancestors, core values, way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In the Huni Kuin and Apurinã communities that inform our case, community members are taught since childhood how to encounter and experience invisible and other life forms, as well as to respect their presences. Even if the active experience of, and interaction with, ungraspable presences in European contexts are different at the personal and collective levels from those of the animal, plant, and other spirit presences in Amazonia, in both places experiences of invisible actors play an important role in the narratives told about the self, about others, and about the world (see also Bergroth et al ; Virtanen ). How these experiences are made evident and true among local people and for authorities is the core question in both of our studies, as in both places they are socially excluded from the dominant society's power regimes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Huni Kuin and Apurinã communities that inform our case, community members are taught since childhood how to encounter and experience invisible and other life forms, as well as to respect their presences. Even if the active experience of, and interaction with, ungraspable presences in European contexts are different at the personal and collective levels from those of the animal, plant, and other spirit presences in Amazonia, in both places experiences of invisible actors play an important role in the narratives told about the self, about others, and about the world (see also Bergroth et al ; Virtanen ). How these experiences are made evident and true among local people and for authorities is the core question in both of our studies, as in both places they are socially excluded from the dominant society's power regimes.…”
Section: Resultsmentioning
confidence: 99%
“…Apurinã have a word for “spirit” ( kamury ) , but spirits are known by their proper names or as a generic term for owner‐master or chief spirits, such as awite . The Apurinã direct their movements in the forest based on the presence of master spirits, as they are highly respected agencies (see Virtanen , ) and can drastically affect human life. A mother of several children commented in a village along the Tumiã River:
Among other things, the children cannot pass close by stones or moriche [buriti, buritiana] palm trees.
…”
Section: Comparing Local Criteria Of Evidence In Differing Onto‐epistmentioning
confidence: 99%
“…Respect among the Manchineri and Apurinã also goes beyond humans, and includes several other-than-human actors. In my research, this has meant recognition of the master spirits of the game and trees, among other things (Virtanen 2019). Respectful approaches to the local other-than-human actors are a crucial tool to keep beings healthy, and disrespecting these norms can cause illnesses, accidents, and unsustainability in the community.…”
Section: Reciprocal Relations In Amazonian Lifeworldsmentioning
confidence: 99%
“…Therefore, the existing written historical records are limited in narrating their past, because research has shown that Manchineri and Apurinã history is entangled with other-than-human actors (Apurinã 2019;Virtanen 2019). As I became a collaborator in the projects addressing the precolonial past, I soon aimed at shedding light on the local Indigenous perspectives and concerns of the research.…”
Section: Reciprocal Relations In Amazonian Lifeworldsmentioning
confidence: 99%
See 1 more Smart Citation